Optimal Portfolio of Liquid 45 Stocks: Single Index Model Approach - Abd Muhni Salam; Augustina Kurniasih (GoAcademica Research & Publishing, 2021)
The purpose of this study is to analyze the return, risk, and optimal portfolio performance of LQ45 stocks formed by a single index model in the period August 2017-January 2020. This research is a descriptive study with a quantitative approach. The data collection technique used is documentation study. Based on the results of the calculation, it is found that out of 33 stocks that met the sample criteria, 3 stocks were selected to compile the optimal portfolio, namely BRPT, ICBP, and BBCA stocks. The stock had expected returns of 5.50%, 1.34%, and 2.02%, respectively, whit a risk of 12.87%, 4.75%, and 4.08%, respectively. The optimal portfolio formed has expected return of 2.60% and risk of 4.05%. After measuring performance with the Sharpe, Treynor, & Jensen approach, it is found that the performance of the portfolios that is formed is better than market performance.